A Simulation of the Viscoelastic Behaviour of Heel Pad During Weight-Bearing Activities of Daily Living - Behforootan, Sara; Chatzistergos, Panagiotis E.; Chockalingam, Nachiappan; Naemi, Roozbeh (Annals of biomedical engineering, 2017)
Internal strain is known to be one of the contributors to plantar soft tissue damage. However, due to challenges related to measurement techniques, there is a paucity of research investigating the strain within the plantar soft tissue during daily weight-bearing activities. Therefore, the main aim of this study was to develop a non-invasive method for predicting heel pad strain during loading. An ultrasound indentation technique along with a mathematical model was employed to calculate visco-hyperelastic structural coefficients from the results of cyclic-dynamic indentation and stress-relaxation tests. Subject-specific structural coefficients of heel pads were calculated from twenty participants along with the assessment of plantar pressure. The average difference between the predicted and the measured force during the cyclic-dynamic indentation test was only 5.8%. Moreover, the average difference between the predicted and the in vivo strain during walking was 14%. No statistically significant correlation was observed between maximum strain and peak plantar pressure during walking; indicating that the measurement of strain along with plantar pressure can improve our understanding of the mechanical behaviour of the plantar soft tissue.